Adhesion-GPCRs: emerging roles for novel receptors. - Yona, S; Lin, H; Siu, W; Gordon, S; Stacey, M (2008)
The G protein-coupled receptor (GPCR) family comprises the largest class of cell surface receptors found in metazoan proteomes. Within the novel GPCR subfamily of adhesion-GPCRs, approximately 150 distinct orthologues, from invertebrates to mammals, have been identified to date. All members of this family contain a large extracellular region, often containing common protein modules, coupled to a seven-transmembrane domain via a stalk region that seems to be crucial for functionality. Owing to their unique structure, restricted expression profile and involvement in several human diseases, adhesion-GPCRs have long been proposed to have vital dual roles in cellular adhesion and signalling. More recent studies have provided structural, evolutionary, developmental and immunological insights in relation to the adhesion-GPCR family.